A methods engineering study on Celdin Shoes MFG. - Casinto, Gerly D. (College of Engineering, 2004)
The different tools in Methods Engineering enabled the group to analyze the documented system of Celdin Shoes Mfg. The core problems were identified and prioritized as follows : (1) poor layout, (2) poor workstation design, and (3) lack of health and safety measures. Alternatives were presented for the solutions of these problems and were evaluated against must and wants objectives. The chosen alternative for the poor layout design in the uppermaking station was the "process layout system" where one line focuses on the production of a particular model of shoes. Supplementing this is the installation of new worktables that can be used in the production of varied shoe designs. A seminar in proper lifting techniques will be conducted to avoid worker injuries. Finally, the uppermaking section will be moved to the second floor and the storage for raw materials will be in the third floor. New work tables will be also installed in the sapatero and finishing sections to respond to the problem of improper dimensions of present worktables and chairs. The Quality control section layout will also be changed. The alternative chosen for this problem was to move the Quality Check area at the end of the finishing line to eliminate excessive walking and material handling. Further studies are recommended for the proper design and dimensions as well as material to be used for the chairs and stools for the workstations and the proposed roller tray for the Sapatero section. To remedy the problem of poor ventilation, the group proposed the use of exhaust fans instead of relying on ceiling fans and stand fans. The group also proposed the use of safety gears like gloves and face masks to prevent prolonged exposure to harmful contact cement fumes. The abovementioned proposals have been addressed to the management. However, their consequent implementation is subject to economic and time constraints.